2013
DOI: 10.3945/jn.112.172395
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression of Endoplasmic Reticulum Resident Selenoproteins Correlates with Apoptosis in Various Muscles of Se-Deficient Chicks

Abstract: Dietary selenium (Se) deficiency causes muscular dystrophy in various species, but the molecular mechanism remains unclear. Our objectives were to investigate: 1) if dietary Se deficiency induced different amounts of oxidative stress, lipid peroxidation, and cell apoptosis in 3 skeletal muscles; and 2) if the distribution and expression of 4 endoplasmic reticulum (ER) resident selenoprotein genes (Sepn1, Selk, Sels, and Selt) were related to oxidative damages in these muscles. Two groups of day-old layer chick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 184 publications
(47 citation statements)
references
References 51 publications
2
45
0
Order By: Relevance
“…Selenium (Se), one of the nutritionally necessary trace elements for a large range of species, exerts a variety of biological effects including immune protection [8] and alleviation of tissue injuries [9,10], and regulates muscle metabolism and apoptosis [11,12], brain function and neuropathology [13], and reproduction [14]. Accordingly, Se deficiency can lead to pathological conditions, including reproductive disorders and inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Selenium (Se), one of the nutritionally necessary trace elements for a large range of species, exerts a variety of biological effects including immune protection [8] and alleviation of tissue injuries [9,10], and regulates muscle metabolism and apoptosis [11,12], brain function and neuropathology [13], and reproduction [14]. Accordingly, Se deficiency can lead to pathological conditions, including reproductive disorders and inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Se deficiency-induced oxidative stress and antioxidant protection of selenoproteins such as GPx are perceived to be involved in the pathogenesis of Se deficiency-related diseases [50]. Cardin et al demonstrated that interactions between SeO 4 2− and MoO 4 2− were competitive for a common intestinal transport mechanism in chick small intestine [51].…”
Section: Discussionmentioning
confidence: 98%
“…Se, an essential dietary micronutrient, plays a pivotal role in many aspects in animal development and health [47,48]. Se are closely related to the NO content [49], iNOS activity in intestine [50], and the mRNA expression of inflammation factors [51] and heat shock proteins [52] in chicken tissues.…”
Section: Discussionmentioning
confidence: 99%